The influence of transformational leadership of school principals and learning communities (kombel) on teachers' professional - Velly Syafriani; Jamilus Jamilus; Dona Afriyani Afriyani (Indonesia Auditing Research Journal, 2026)
This research is motivated by the phenomenon of increasing teacher professional competence, which is suspected to be influenced by the transformational leadership of the principal and the learning community (kombel). The purpose of this study is to determine the positive and significant influence of the transformational leadership of the principal and the learning community (kombel) on teacher professional competence. This study uses a quantitative correlation approach with a population of 970 teachers. A sample of 283 teachers was taken using a probability sampling technique through proportional cluster sampling in each school. The instrument used in this study was a questionnaire. Instrument development was carried out through several stages, namely the preparation of the instrument grid, validity testing, and reliability testing. The questionnaire was distributed to respondents using Google Forms. Data analysis techniques were carried out using the classical assumption test as a prerequisite, followed by hypothesis testing using simple linear regression and multiple linear regression. The results of the study indicate that the transformational leadership of the principal influences the professional competence of junior high school teachers in Limapuluh Kota Regency, the learning community (kombel) influences the professional competence of junior high school teachers in Limapuluh Kota Regency, and the transformational leadership of the principal and the learning community (kombel) jointly influences the professional competence of junior high school teachers. Therefore, school principals need to optimize the implementation of transformational leadership and increase learning community (kombel) activities on an ongoing basis to support the improvement of teachers' professionalism.